Cellular strategies for repairing trapped protein-DNA complexes - Sideridou, Maria; Machli, Doukissa Ioanna; Lontra, Dora; Rampias, Theodoros (Frontiers in Pharmacology, 2026)
DNA-protein crosslinks (DPCs) are highly toxic DNA lesions that arise both from normal cellular metabolism and as an intended consequence of cancer chemotherapy. Key anticancer agents, including topoisomerase poisons and PARP inhibitors, exert their therapeutic effects by trapping enzymes on DNA, converting them into toxic barriers that block replication. To counteract this threat, cells have evolved specialized mechanisms to detect and remove DPCs. This review explores the molecular mechanisms by which these therapies trap proteins on DNA and the multi-layered defense systems cells use to resolve them-ranging from enzymatic degradation to mechanical extraction. We further examine how these processes are modulated by the cell cycle and chromatin landscape. Importantly, we highlight emerging evidence that alterations in DPC repair pathways are frequent in cancer and serve as critical determinants of treatment response. Ultimately, this review integrates mechanistic insights with clinical data to highlight how exploiting DPC repair defects can overcome drug resistance and guide the development of rational, synthetic lethal combination therapies.